2020
DOI: 10.3390/ijms21207528
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the VEGF-A/ERK/PLA2 Axis Mediates Early Retinal Endothelial Cell Damage Induced by High Glucose: New Insight from an In Vitro Model of Diabetic Retinopathy

Abstract: Early blood retinal barrier (BRB) dysfunction induced by hyperglycemia was related to increased pro-inflammatory activity of phospholipase A2 (PLA2) and the upregulation of vascular endothelial growth factor A (VEGF-A). Here, we tested the role of VEGF-A in high glucose (HG)-induced damage of human retinal endothelial cells (HRECs) mediated by Ca++-dependent (cPLA2) and Ca++-independent (iPLA2) PLA2s. HRECs were treated with normal glucose (5 mM, NG) or high glucose (25 mM, HG) for 48 h with or without the VEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 62 publications
6
29
0
Order By: Relevance
“…Many years of research have shown that hyperglycaemia plays a central role in the induction of diabetic retinopathy [ 18 , 19 , 20 ]. Studies conducted in non-obese diabetic mice (NOD mice) have demonstrated that the first changes on the fundus of the eye blood–retinal barrier breakdown are observed already in the first week of exposure to high glucose levels [ 21 ].…”
Section: The Retina—hyperglycaemia and Inflammation In The Course mentioning
confidence: 99%
See 1 more Smart Citation
“…Many years of research have shown that hyperglycaemia plays a central role in the induction of diabetic retinopathy [ 18 , 19 , 20 ]. Studies conducted in non-obese diabetic mice (NOD mice) have demonstrated that the first changes on the fundus of the eye blood–retinal barrier breakdown are observed already in the first week of exposure to high glucose levels [ 21 ].…”
Section: The Retina—hyperglycaemia and Inflammation In The Course mentioning
confidence: 99%
“…Studies conducted in non-obese diabetic mice (NOD mice) have demonstrated that the first changes on the fundus of the eye blood–retinal barrier breakdown are observed already in the first week of exposure to high glucose levels [ 21 ]. In the environment of high glucose concentration, hyperglycaemia causes cell dysfunction, retinal neurovascular impairment, structural defects and functional disorders which lead to further damage of the retinal cells [ 13 , 18 , 19 ]. The next active stage of pathological changes is associated with the inflammatory process [ 22 , 23 , 24 ].…”
Section: The Retina—hyperglycaemia and Inflammation In The Course mentioning
confidence: 99%
“…Hyperglycemia is an important risk factor for the occurrence and development of DR, which can cause damage to retinal microvascular system, including capillary swelling and deformation, Blood retinal barrier (BRB) damage. In the environment of high glucose concentration, hyperglycemia leads to cell dysfunction, retinal vascular and nerve damage, structural defects and further damage of retinal cells, functional disorders (31)(32)(33). Ages binding to rage induce a strong intracellular signal transduction cascade, leading to endothelial dysfunction, key pro-in ammatory cytokines and pro angiogenic factors, such as tumor necrosis factor -α (TNF -α) and nuclear transcription factor -kB (NF -kb) Activation of NFkb mediates pericyte apoptosis, vascular in ammation and angiogenesis, as well as the destruction of endogenous BRB.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor-A-encoding ( VEGF-A ) gene transcription leads to multiple alternative splicing isoforms resulting in either anti- or pro-angiogenic properties GF [ 191 , 192 ]. In humans, VEGF-A is physiologically expressed in testis, seminal vesicles, prostate, measurable in the seminal fluid, and involved in the control of male reproductive functions [ 193 ].…”
Section: Endothelial Function and Male Fertility: Inflammation Marmentioning
confidence: 99%